Research of viscoelastic and hygroscopic properties of adhesive, textile materials and packages based on them - Natalia Bereznenko; Larysa Bilotska; Halina Szafranska (Communications in Development and Assembling of Textile Products, 2024)
Materials with multifunctional properties are the future of modern clothing, and the creation of such materials is extremely urgent. When creating such materials, it is appropriate to use non-woven nano-modified materials as components of clothing details. At the same time, it is important to ensure the viscoelastic and hygroscopic properties of packages of materials for making clothes. This study presents the analysis of these important properties of tissue packages depending on the parameters of their duplication.